Three birds with one stone: a disintegrable fertilizer with rapid fertilization, controlled-loss and detoxification - Xianghai Kong; Chen Sun; Ziyu You; Wanji Zhu; Xinxin Zhai; Yuhao Wang; Yan Wang; Weijian Zhang; Kaimin Zhu; Xiaoshuang Han; Pan Zhao; Yanping Zhu; et al. (Desalination, 2026)

Untargeted serum lipidomics reveals lipid metabolic disturbances and identifies candidate lipid biomarkers in acute diquat poisoning - Xinxin Huang; Xunan Kan; Lei Xiao; Chuanguang Han; Ge Li; Quan Xia; Qianli Zou; Qinhai Ma; Shuai Song (Toxicology and Applied Pharmacology, 2026)

Hydrogen bond-assisted rapid ammonium ion transport in Prussian blue electrochromic devices - Bingkun Huang; Feifei Zhao; Long Zhang; Yukai Xu; Jiashuo Li; Qilin Wei; Xinxin Han; Litao Kang; Jia-Yue Yang; Wu Zhang; Jingwei Chen; William W. Yu (Chemical Engineering Journal, 2026)

Enhanced solubility of yeast protein via high-pressure homogenization-assisted limited enzymatic hydrolysis: mechanisms of structural modification and implications for functionality and nutrition - Zhaowei Han; Bingyu Chen; Xinxin Li; Xuchun Zhu; Zhongjiang Wang; Jingwen Zhu; Yan Zhao; Chao Yan; Faying Zheng; Mingzheng Huang; Linyi Zhou; Hongzhi Liu (Food Research International, 2026)

Changes in the gluten protein aggregation properties during resting under the regulation of wheat A/B starch ratio and dietary fiber particle size - Faying Zheng; Xuchun Zhu; Yuanqiang Jia; Bingyu Chen; Xinxin Li; Mengying Liu; Zhaowei Han; Hongzhi Liu (Food Hydrocolloids, 2026)

A multifunctional PPy/GO/PVDF photothermal membrane for solar-driven water purification coupled with dye desalination - Yang Li; Yumin Sun; Xinxin Cao; Xutong Han; Hailiang Liu (Desalination, 2026)

Machine learning-enabled bimodal flexible tactile sensors for intelligent contact-noncontact recognition - Defan Wang; Yi Zhao; Xinxin Zhao; Chengfu Han; Kangkang Zhou; Yajie Zhang; Wei Zhai; Guoqiang Zheng; Jianwei Xu; Kun Dai; Chuntai Liu; Changyu Shen (Chemical Engineering Journal, 2026)

Mitochondrial genome and phylogenetic analysis of Aster Indicus L. - Ying Meng; Yuting Liang; Kaiyue Wang; Youjuan Zhu; Xinxin Zhao; Tong Zhang; Jingyu Yang; Fei Han; Juan Wang; Jiangtao Wu; Xiaofeng Shen (Genetica, 2026)

Erratum to “Untargeted serum lipidomics reveals lipid metabolic disturbances and identifies candidate lipid biomarkers in acute diquat poisoning” [Toxicology and Applied Pharmacology 516 (2026) 117995] - Xinxin Huang; Xunan Kan; Lei Xiao; Chuanguang Han; Ge Li; Quan Xia; Qianli Zou; Qinhai Ma; Shuai Song (Toxicology and Applied Pharmacology, 2026)

Decreased burial of organic carbon in ferruginous-prevailing cold seeps - Can Chen; Xiaoming Miao; Davide Oppo; Fei Han; Qianwen Xiao; Hongxiang Guan; Xinxin Cao; Qing Wang; Sanzhong Li (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Nitrogen and oxygen co-doped porous carbon prepared via two-step thermal melting-carbonization for ammonium-ion supercapacitors - Yahui Gao; Huijun Tan; Huajun Chen; Shuxia Zhang; Yanjie Xu; Xinxin Yang; Yalei Miao; Yi Wang; Jiacan Han; Huiyi Liu; Wenjie Tian (Chemical Engineering Journal, 2026)

Zonarol, a sesquiterpene from the brown algae Dictyopteris undulata, alleviates rotenone-induced Parkinson's disease via modulation of the Keap1/Nrf2 signaling pathway - Xinxin Liu; Ruiqi Zhang; Yi Liu; Jia Han; Sohsuke Yamada; Tomoyuki Koyama (Algal Research, 2026)

The health threat of wild animals by Rank I ARGs from habitat soils: Metagenomic and metabolomic evidence - Jiaying Ma; Han Zhang; Sumei Liang; Xinxin Feng; Zhaoyang Xia; Hong Li; Shuzhen Zou; Dayong Li (Environmental Pollution, 2026)

Integrated end-to-end continuous-flow platform for the process intensification and kilogram-scale production of TADF emitters - Xiaoyan Li; Shoujia Zhu; Ying Wei; Yang Li; Zheng Zhang; Hao Li; Yugang Chen; Yun Deng; Xinxin Han; Quanyou Feng; Linghai Xie (Chemical Engineering Journal, 2026)

Evolution of single-particle morphology and composition from typical bituminous coal combustion under different temperatures - Junjie Cai; Jun Zeng; Yingjun Chen; Haoran Ma; Hongxing Jiang; Yu Peng; Feiyan Cao; Yong Han; Zeyu Liu; Xinxin Feng (Atmospheric Environment, 2026)

Kinetic Modelling of the Decay of Respiratory Syncytial Viruses (RSV) Facilitated a Robust Wastewater-Based Surveillance for RSV - Yuqing Long; Jiayi Liu; Xiuyuan Shi; Xueling Yang; Yongyan Long; Jinzhou Xiao; Xinxin Han; Songzhe Fu (Food and Environmental Virology, 2026)

Dynamic dose–time proteomic profiling of cadmium exposure in rat prefrontal cortex - Zhijian Hu; Feng Han; Hao Gao; Sheng Wan; Hui Liu; Li Jie; Yinghui Yin; Maoqin Tian; Yong Yang; Wenjie Chen; Xiao Tan; Xinxin Shi; et al. (NeuroToxicology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Trade-off-free intrinsically stretchable electroluminescent films enabled by a thermally activated delayed fluorescence plasticizer - Wenzhong Bian; Xinxin Ban; Junyi Chen; Mengting Li; Caixia Yang; Hongyu Zhuang; Shuang Chen; Jiangqi Jiang; Wenli Shi; Hai Zhou; Youqiang Qian; Zhaoxiang Han; et al. (Chemical Engineering Journal, 2026)

Improvement of dough rheological behavior and overall product quality through incorporation of physically modified dietary fiber polysaccharides: A review - Faying Zheng; Xinxin Li; Zhaowei Han; Xuchun Zhu; Pengtao Zhang; Feiyue Ren; Hongzhi Liu (Carbohydrate Polymers, 2026)

Combined histopathological, immunoenzymatic and transcriptomic analyses reveal the immune response mechanisms of silver pomfret infected by Vibrio parahaemolyticus - Dianyang Zhou; Ping Han; Yadong Xue; Zhennan Sun; Longdi Wang; Xiumei Liu; Jianming Chen; Yajun Wang; Suming Zhou; Xue Sun; Xinxin Du; Xubo Wang (Fish & Shellfish Immunology, 2026)

Na+-preintercalated α-MnO2 for printed electrodes of aqueous hybrid supercapacitors - Shang Wang; Yuhang Han; Xinyang Ma; Zirui Tong; Xinxin Wang; Meng Xie; Qing Sun; Jiayun Feng; Yanhong Tian (Chemical Engineering Journal, 2026)

3,3'-Dichlorobiphenyl (PCB 11) alters the hepatic expression of cytochrome P450 enzymes in the liver of mouse dams exposed orally during pregnancy and lactation - Crystal M. Roach; Nate R. Koester; Xueshu Li; Jeonghyeon Ahn; R. Marshall Pope; Rebecca J. Wilson; Rosalia Mendieta; Anthony Valenzuela; Weiguo Han; Xinxin Ding; Pamela J. Lein; Hans-Joachim Lehmler (Archives of Toxicology, 2026)
Healthy maternal metabolism is critical during pregnancy and lactation to support fetal development and protect against environmental toxins. Polychlorinated biphenyl 11 (PCB 11), a lower-chlorinated, non-legacy congener, is detected in human serum, including pregnant women and children; however, its impact during these sensitive life stages remains poorly understood. This study presents the first comprehensive hepatic proteome analysis of mouse dams exposed to PCB 11 during pregnancy and lactation. Female C57BL/6 J mice received daily oral doses of PCB 11 (0, 1.0 or 6.0 mg/kg) prior to conception through lactation. At postpartum day 21, brain, liver, and serum samples were analyzed for PCB 11 and its metabolites, and hepatic proteomic changes were assessed. Low detection of PCB 11 and its metabolites was observed in tissues, suggesting rapid clearance. Metabolite screening revealed OH-PCB 11, PCB 11 sulfate, and OH-PCB 11 sulfate metabolites in serum. Global proteomics identified significant alterations in hepatic protein expression, including downregulation of cytochrome P450 enzymes, solute carriers, and enzymes involved in fatty acid and steroid metabolism. Pathway enrichment analyses indicated disruptions in xenobiotic metabolism and endocrine pathways. These findings suggest that PCB 11 exposure during pregnancy and lactation impairs hepatic detoxification and metabolic capacity, potentially compromising maternal and offspring health. This work highlights the need for further investigation into the long-term consequences of PCB 11 exposure during pregnancy and lactation.

Atmospheric aging enhances PAH-associated carcinogenic potency in the ultrafine size range of biomass-burning organic aerosol via oxygenated PAH formation - Yu Peng; Hongxing Jiang; Yingjun Chen; Yong Han; Xinxin Feng; Junjie Cai; Yishun Zhang; Zeyu Liu; Feiyan Cao; Tian Chen (Journal of Hazardous Materials, 2026)

A review of synergistic strategies for photothermal catalytic VOCs degradation: Catalyst design and reaction system optimization - Dan Zhang; Tao Han; Fahui Wang; Xinxin Han; Shuxian Yin; Fang Liu; Ziyi Jing; Guanyi Chen (Journal of Environmental Chemical Engineering, 2026)

Melittin nanoparticle-based bidirectional sprayable thermosensitive chitosan hydrogel for immediate post-surgical breast cancer therapy - Ye Liu; Xinxin Chang; Kailian Zhang; Yiping Liang; Han Zhou; Haili Wang; Hangyi Wu; Tao Chen; Xin Jin (Chemical Engineering Journal, 2026)

Rational design of type-I p-CuO/n-NUS-8 heterojunctions for highly selective photocatalytic CO2 reduction to CH4 - Xin Huang; Zuoyi Wang; Ying Jiang; Wenwen Wen; Shixia Chen; XinXin Han; Jingwen Chen; Shuguang Deng; Jun Wang (Chemical Engineering Journal, 2026)

Electrode interfacial wettability engineering for high-efficiency synthesis of dimethyl sebacate via Kolbe electrolysis - Linchuan Cong; Xinxin Li; Fuyu Han; Yupeng Wu; Kewen Ma; Ciduo Wang; Nan Lin; Haibo Lin (Chemical Engineering Journal, 2025)

Bimetallic Fe/Mn MOFs derivatives loaded on biochar for activated peroxydisulfate in degradation of sulfamethoxazole: Fe-Mn bonding promotes non-radical pathway transitions - Yuying Han; Jiuwan Wang; Xinxin Yan; Dandan Wang; Hongkun Han; Congting Sun (Journal of Hazardous Materials, 2025)

Peripheral blood RNA modifications as a novel diagnostic signature for polycystic ovary syndrome - Liwen Zhang; Xinxin Liu; Yu Zhang; Lang Qin; Shijia Pan; Xueqi Yan; Sen Dong; Zerong Feng; Song-jia Fan; Rusong Zhao; Xueying Gao; Shigang Zhao; et al. (Science China Life Sciences, 2025)

Oxygenated aromatic compounds as dominant contributors to the oxidative potential of PM2.5 emitted from biomass burning and coal combustion - Feiyan Cao; Xinxin Feng; Yingjun Chen; Hongxing Jiang; Yong Han; Tian Chen; Yu Shang; Dan Li; Qianyu Zhang; Huimin Ma; Jun Li; Gan Zhang (Journal of Hazardous Materials, 2025)

Effects of different plastics on pollutant removal and microbial community structure in vertical flow constructed wetland - Guolan Han; Song Li; Xinxin Jing; Yifan Zhao; Yuanyuan Shao; Lei Liu; Zhao Li; Hongbo Wang (Journal of Environmental Chemical Engineering, 2025)

Halide anions-facilitated structural manipulation in Mn-based hybrids for multicolor emission and X-ray imaging - Tong Chang; Tongtong Kou; Qilin Wei; Liang Wang; Xiulian Cai; Huanxin Su; Yuanxiang You; Xin Li; Xinxin Han; Shiguo Han; William W. Yu (Chemical Engineering Journal, 2025)

Distributional characteristics and causes of single-layer stratiform clouds over typical region in the southeastern Pacific Ocean - Ximing Deng; Yong Han; Chunsong Lu; Xinxin Xie; Yurong Zhang; Tianwei Lu; Li Dong; Qicheng Zhou (Atmospheric Research, 2025)

Late-Stage Activation of Toll-like receptor 3 Alleviates Cognitive Impairment and Neuropathology in an Alzheimer’s Disease Mouse Model - Taiyang Zhu; Fanyu Shen; Xiao Jia; Hui Zhou; Wanyan Ni; Shang Wang; Di Wu; Huimin Gao; Zhenying Shang; Yan Zhou; Jingjing Han; Guoliang Jin; et al. (Molecular Neurobiology, 2025)

The mechanisms of hypoxia formation in a major tributary of the Three Gorges Reservoir, China - Siqian Qiu; Hui Xu; Lianghong Long; Yanxing Han; Yubo Huang; Xinxin Ji; Linxu Song; Xingxing Zhao; Zhongyong Yang; Xinbo Liu; Andreas Lorke; Daobin Ji (Journal of Hydrology, 2025)

Potassium-doping double perovskite with improved oxygen reaction activity and durability cathode for dual-function ceramic electrochemical cells - Ao Zhao; Fangjun Jin; Wenjing Zhang; Yaqiong Guo; Zhen Wang; Ning Sun; Yuan Gao; Fangshen Liu; Xinxin Wang; Kun Zheng; Donglin Han; Yihan Ling (Chemical Engineering Journal, 2025)

Mutations of two AhTT8 genes reduce the accumulation of anthocyanins and confer the white testa of peanut (Arachis hypogaea L.) - Hailing Zi; Yaxin Ding; Ruiyuan Fang; Xinxin Li; Zhiyuan Song; Huailing Huang; Nana Li; Shoujin Fan; Chuanzhi Zhao; Xingjun Wang; Han Xia (Theoretical and Applied Genetics, 2025)

Advancements in the investigation of the mechanisms underlying cognitive aging - Honglu Zou; Shuo Zhang; Xinxin Cui; Hongyan Xu; Zhangying Zhou; Danmeng Cheng; Yanan Han; Youcai Tang; Anqin Dong; Xianwen Dong (Biogerontology, 2025)

Physiological and transcriptomic analysis of tomato leaf mold resistance gene Cf-12 against Cladosporium fulvum - Xinyu Zhang; Han Liu; Xinxin Xie; Menglin Sun; Nanshan Du; Dongqi Xue (Physiological and Molecular Plant Pathology, 2025)

Key toxicity enhancement effect of aqueous-phase secondary formation: Insights from hourly measurements during haze events - Feiyan Cao; Yingjun Chen; Yong Han; Tian Chen; Xinxin Feng; Hongxing Jiang; Qianyu Zhang; Huimin Ma; Jun Li; Gan Zhang (Journal of Hazardous Materials, 2025)

Effects of long-term biochar addition on the wheat-rotated rice grain yield and the fate of N fertilizer in plant-soil system—A combined 15N study - Zhi Wang; Xinyu Liu; Jiawen Han; Bo Xu; Wei Ma; Yunfei Lu; Xinxin Ye (European Journal of Agronomy, 2025)

The role of LNK in mitigating hypertension: inhibition of vascular smooth muscle proliferation and JAK-STAT pathway - Xinxin Han; Shuo Wei; Ali Ahmad; Yibo Cao; Caihong Zhao; Mengyang Yan; Jing Zhao; Xingmei Deng; Hongsu He; Zhihua Sun (Molecular and Cellular Biochemistry, 2025)

Bio-Organic Fertilizer Decreased Soil Carbon Mineralization by Altering Humus Fraction in a Greenhouse Soil - Lijun Ren; Han Yang; Xinxin Jin; Yanyu Han; Jiaqi Li; Yifeng Zhang; Hongtao Zou; Yulong Zhang (Journal of Soil Science and Plant Nutrition, 2025)

Formaldehyde oxidation reaction enhanced by interface engineering of Cu/Cu2O/Co(OH)2 composite electrocatalyst for bipolar hydrogen production - Zi Qiang Ma; Chang Bao Han; Wen Kang Zhao; De Cai Fang; Yi Lin Zhao; Chang Xin Liu; Xinxin Wang; Ling Sun; Xue Mei Song (Chemical Engineering Journal, 2025)

Habitat preference drives the community composition, beta diversity and assembly processes of benthic diatoms: A case study of a wetland cluster in a cold region - Yongxu Duan; Zheng Hou; Shuangyu Han; Henglin Xiao; Yan Liu; Yawen Fan; Xinxin Lu (Environmental Research, 2025)

UV-aging process of titanium dioxide nanoparticles aggravates enterohepatic toxicity of bis(2-ethylhexyl)-2,3,4,5-tetrabromophthalate to zebrafish - Yuxi Zhou; Kaiyu Fu; Fan Li; Yindan Zhang; Xinxin Ren; Bingjie Li; Shengmin Wu; Jian Han; Lihua Yang; Bingsheng Zhou (Science of The Total Environment, 2025)

Monoclonal antibody development and antigenic epitope identification of infectious bursal disease virus VP5 - Jinze Han; Xinxin Niu; Chengfei Ge; Ziwen Wu; Guodong Wang; Mengmeng Huang; Yulong Zhang; Runhang Liu; Mengmeng Xu; Hangbo Yu; Jingzhe Han; Suyan Wang; et al. (The Veterinary Journal, 2024)

Modelling of the trade-off between the deep soil moisture and vegetation restoration in the hilly area of the Loess Plateau, China - Yuqing Chang; Lei Han; Rui Chen; Zhao Liu; Yabei Li; Zilin Zhao; Yifeng Gao; Meili Yang; Xinxin Cao; Zheyuan Miao; Hongliang Kang (Journal of Hydrology, 2024)

Environmentally relevant concentrations of perfluorobutane sulfonate impair locomotion behaviors and healthspan by downregulating mitophagy in C. elegans - Yahui Shang; Kelie Chen; Heng Ni; Xiaoyu Zhu; Xiaoyu Yuan; Yuwei Wang; Xinxin Liu; Zhenyan Cui; Yuequn Niu; Yu Shi; Han Wu; Dajing Xia; et al. (Journal of Hazardous Materials, 2024)

Nano boron carbide effectively boost Fenton-like performance of hematite mediated systems: Roles of hematite exposed facets and synergistic catalysis between Fe and B - Yulu Zhang; Huali Yu; Guangfei Liu; Haiyan Guo; Song Yan; Lei Han; Xinxin Jin; Qing Luo; Lianfeng Wang (Environmental Pollution, 2024)

Pathophysiology, molecular mechanisms, and genetics of atrial fibrillation - Pan Han; Xinxin Zhao; Xuexun Li; Jing Geng; Shouxiang Ni; Qiao Li (Human Cell, 2024)

Decomposing high uncertainty in greenhouse gas mitigation pathways in emerging regions: An approach to evaluate risks toward carbon neutrality - Hui Han; Xinxin Ye; Yahui Bian; Shuifa Lin; Yu-Sheng Shen; Zhi Huang; Jianyi Lin (Science of The Total Environment, 2024)

Isolation and characterization of Bifidobacterium spp. from breast milk with different human milk oligosaccharides utilization and anti-inflammatory capacity - Xinxin Ma; Jianhui Mo; Lu Shi; Yue Cheng; Jiayu Feng; Jiale Qin; Wanghong Su; Jia Lv; Shaoru Li; Qiang Li; Hui Tan; Bei Han (Food Research International, 2024)

Overexpression of a Malus baccata (L.) Borkh WRKY transcription factor gene MbWRKY65 increased the tolerance to cold and drought in transgenic tomato - Chunwen Yu; Anqi Yao; Xingguo Li; Wenhui Li; Ruina Gao; Yuqing Feng; Zhuxuan Li; Xinxin Guo; Lihua Zhang; Deguo Han (In Vitro Cellular & Developmental Biology - Plant, 2024)

Identification of Floating Green Tide in High-Turbidity Water from Sentinel-2 MSI Images Employing NDVI and CIE Hue Angle Thresholds - Lin Wang; Qinghui Meng; Xiang Wang; Yanlong Chen; Xinxin Wang; Jie Han; Bingqiang Wang (Journal of Marine Science and Engineering, 2024)
Remote sensing technology is widely used to obtain information on floating green tides, and thresholding methods based on indices such as the normalized difference vegetation index (NDVI) and the floating algae index (FAI) play an important role in such studies. However, as the methods are influenced by many factors, the threshold values vary greatly; in particular, the error of data extraction clearly increases in situations of high-turbidity water (HTW) (NDVI > 0). In this study, high spatial resolution, multispectral images from the Sentinel-2 MSI mission were used as the data source. It was found that the International Commission on Illumination (CIE) hue angle calculated using remotely sensed equivalent multispectral reflectance data and the RGB method is extremely effective in distinguishing floating green tides from areas of HTW. Statistical analysis of Sentinel-2 MSI images showed that the threshold value of the hue angle that can effectively eliminate the effect of HTW is 218.94°. A test demonstration of the method for identifying the floating green tide in HTW in a Sentinel-2 MSI image was carried out using the identified threshold values of NDVI > 0 and CIE hue angle 0), resulting in better consistency of the identification of the floating green tide and its distribution in the true color image. The method enables rapid and accurate extraction of information on floating green tide in HTW, and offers a new solution for the monitoring and tracking of green tides in coastal areas.

Examining starch metabolism in lotus roots (Nelumbo nucifera Gaertn.) during post-harvest storage at different temperatures - Xinxin Gong; Ruiling Liu; Yanchao Han; Ben Niu; Weijie Wu; Huizhi Chen; Xiangjun Fang; Honglei Mu; Haiyan Gao; Hangjun Chen (Food Chemistry, 2024)

Preharvest GA3 treatment at optimized time points enhanced the storability of ‘Shixia’ longan fruit - Tao Luo; Libing Long; Tingting Lai; Xiaolan Lin; Chenning Ning; Ziying Lai; Xinxin Du; Liang Shuai; Dongmei Han; Zhenxian Wu (Postharvest Biology and Technology, 2024)

Loop PDE of viral capsid protein is involved in immune escape of the emerging novel variant infectious bursal disease virus - Guodong Wang; Nan Jiang; Hangbo Yu; Xinxin Niu; Mengmeng Huang; Yulong Zhang; Wenying Zhang; Jinze Han; Mengmeng Xu; Runhang Liu; Ziwen Wu; Jingzhe Han; et al. (Veterinary Microbiology, 2024)

Physiological and molecular mechanism of Populus pseudo-cathayana × Populus deltoides response to Hyphantria cunea - Yutong Ding; Jiajia Shen; Hanxi Li; Yue Sun; Tingbo Jiang; Xiangbo Kong; Rui Han; Chunli Zhao; Xinxin Zhang; Xiyang Zhao (Pesticide Biochemistry and Physiology, 2024)

High starch and hemicellulose labile C degradation functional genes increase soil CO2 emissions follow straw return - Jin Li; Jiaqi Li; Xuhong Ye; Bol Roland; Xinxin Jin; Yanyu Han; Na Yu; Hongtao Zou (Applied Soil Ecology, 2024)

Unleashing the potential of short-chain fatty acids: Alginate-degrading consortium boosts anaerobic sludge fermentation - Kaili Ma; Qiujuan Li; Xinxin Han; Yiru Du; Yifan Jiang; Xu Yan; Yanrui Cui; Wei Kang; Lingwei Meng; Zhiguo Cao (Journal of Environmental Chemical Engineering, 2024)

Aging of polypropylene plastic and impacts on microbial community structure in constructed wetlands - Xinxin Jing; Yuanyuan Shao; Hongbo Wang; Guolan Han; Jian Zhang; Ning Wang; Jingtao Xu; Lei Liu; Gao Chen (Environmental Pollution, 2024)

PM2.5 air quality and health gains in the quest for carbon peaking: A case study of Fujian Province, China - Yahui Bian; Xiaobo Huang; Shuifa Lin; Hui Han; Jinsheng Chen; Jianyi Lin; Xinxin Ye (Science of The Total Environment, 2024)

Full-length transcriptome profiling of Acanthopanax gracilistylus provides new insight into the kaurenoic acid biosynthesis pathway - Bing He; Tingyu Shan; Jingyao Xu; Xinxin Zhong; Jingjing Zhang; Rongchun Han; Qingshan Yang; Jiawen Wu (Physiology and Molecular Biology of Plants, 2024)

Clinical landscape and prognosis of patients with gastric cancer liver metastases: A nation-wide multicenter cohort study in China (RECORD study) - Yunhe Gao; Hongqing Xi; Liang Shang; Zhaoqing Tang; Bo Wei; Zhi Qiao; Yun Tang; Xinxin Wang; Jing Zhou; Xuefei Wang; Changming Huang; Jun Lu; et al. (Science Bulletin, 2024)

Improved anaerobic sludge fermentation mediated by a tryptophan-degrading consortium: Effectiveness assessment and mechanism deciphering - Kaili Ma; Xinxin Han; Qiujuan Li; Yu Kong; Qiaoli Liu; Xu Yan; Yahong Luo; Xiaopin Li; Huiyang Wen; Zhiguo Cao (Journal of Environmental Management, 2024)

Boosting decarboxylation of monomethyl adipate coupling to dimethyl sebacate through Pt electrode at high current density - Linchuan Cong; Yupeng Wu; Nan Lin; Xinxin Li; Fangbing Liu; Fuyu Han; Jin Yang; Ciduo Wang; Haibo Lin (Chemical Engineering Journal, 2024)

Novel layer-to-layer charge transfer in an anion-pillared metal-organic framework for efficient CO2 photoreduction to CH4 - Xinxin Han; Hongtao Wu; Shixia Chen; Shuguang Deng; Jun Wang (Chemical Engineering Journal, 2024)

Antimicrobial Peptides Targeting Streptococcus mutans: Current Research on Design, Screening and Efficacy - Xinxin Ying; Guanglu Xue; Pengxiang Sun; Ziling Gan; Ziqian Fan; Bo Liu; Yaoting Han; Jiaqian Yang; Jing Zhang; Aiping Lu (Current Microbiology, 2024)

Air particulate pollution exposure associated with impaired cognition via microbiota gut-brain axis: an evidence from rural elderly female in northwest China - Jia Yuan; Hui Tan; Yue Cheng; Xinxin Ma; Sijin Jiang; Xinyao Hou; Shaoru Li; Lu Shi; Pu Li; Hongmei Xu; Jia Lv; Bei Han (Environmental Science and Pollution Research, 2023)

Highly stable multi-responsive yellow-emissive fluoride RbCdF3:Mn2+,Yb3+ for advanced optical anti-counterfeiting - Chuanyu Zeng; Xinxin Han; Enhai Song; Dongxi Liu; Chao Liu; Juan Wang; Sheng Cao; Ruosheng Zeng; Jialong Zhao; Bingsuo Zou (Chemical Engineering Journal, 2023)

SlbHLH152, a bHLH transcription factor positively regulates iron homeostasis in tomato - Xiaoli Li; Haohao Cao; Deshui Yu; Kedong Xu; Yi Zhang; Xinxin Shangguan; Xiaohong Zheng; Zhongzhou Yang; Chaoqiong Li; Xingchen Pan; Yiming Cui; Zhiqing Zhang; et al. (Plant Science, 2023)

Study on properties of TGase-induced pea protein–zein complex gels - Yilin Zhao; Xinxin Han; Nannan Hu; Chengbin Zhao; Yuzhu Wu; Jingsheng Liu (Journal of Food Engineering, 2023)

Nationwide occurrence and distribution of liquid crystal monomers in municipal sewage sludge of China - Zhiqing Feng; Bibai Du; Mingjie Shen; Xu Han; Xinxin Liang; Lixi Zeng (Science of The Total Environment, 2023)

Porous polymer magnetic adsorbents for dye wastewater treatment - Tao Xue; Feifei Shao; Han Miao; Xinxin Li (Environmental Science and Pollution Research, 2023)

Strategies for controlling gas evolution reactions to boost the divergent paired electrochemical upgrading of furfural in acidic environment - Xinxin Li; Linchuan Cong; Yupeng Wu; Nan Lin; Fangbing Liu; Deyuan Xin; Fuyu Han; Jin Yang; Weitong Chen; Haibo Lin (Chemical Engineering Journal, 2023)

Circular RNA circAKIRIN2 participates in the process of stress-induced immunosuppression affecting immune response to infectious bursal disease virus vaccine in chicken - Yufei Tian; Xiaoli Ma; Yi Jiang; Jianwei Han; Rui Zhang; Xinxin Xu; Wei Zhang; Chaolai Man (Veterinary Microbiology, 2023)

Characteristics analysis of plastisphere biofilm and effect of aging products on nitrogen metabolizing flora in microcosm wetlands experiment - Jian Zhang; Yuanyuan Shao; Zhao Li; Guolan Han; Xinxin Jing; Ning Wang; Jingtao Xu; Gao Chen (Journal of Hazardous Materials, 2023)

Novel nanozyme Ag/Fe3O4@h-BN with peroxidase-mimicking and oxidase-mimicking activities for dye degradation, As(V) removal and detection - Ziming Xin; Kaifeng Duan; Qizheng Zhuo; Qianqian He; Xiao Zhang; Chuanjun Zheng; Xiaoyu Han; Tianfang Han; Zhongtian Fu; Xinxin Xu; Xin Zhao (Chemical Engineering Journal, 2023)

Porous and graphitic structure optimization of biomass-based carbon materials from 0D to 3D for supercapacitors: A review - Xiaohua Zhang; Ruyun Han; Yanzhen Liu; Hengxiang Li; Wenjing Shi; Xiaoyan Yan; Xinxin Zhao; Yongfeng Li; Baosheng Liu (Chemical Engineering Journal, 2023)

Trace elements in outdoor and indoor PM2.5 in urban schools in Xi’an, Western China: characteristics, sources identification and health risk assessment - Runyu Wang; Xinxin Ding; Jingzhi Wang; Zhibao Dong; Hongmei Xu; Ge Ma; Bo Gao; Han Song; Menghan Yang; Junji Cao (Environmental Geochemistry and Health, 2023)

An aging giant at the center of global warming: Population dynamics and its effect on CO2 emissions in China - Hongwei Guo; Jia Jiang; Yuanyuan Li; Xinxin Long; Ji Han (Journal of Environmental Management, 2023)

In-situ growth of Co/Zn bimetallic MOF on GO surface to prepare GO supporting Co@C single-atom catalyst for Hg0 oxidation - Xiaopeng Zhang; Xiangkai Han; Cheng Gao; Xinxin Wang; Yuying Wei; Ning Zhang; Junjiang Bao; Ning Xu; Gaohong He (Fuel, 2023)

Nanomaterials in agricultural soils: Ecotoxicity and application - Chuanxin Ma; Lanfang Han; Heping Shang; Yi Hao; Xinxin Xu; Jason C. White; Zhenyu Wang; Baoshan Xing (Current Opinion in Environmental Science & Health, 2023)

Geraniin targeting CaMKK2 inhibits lipid accumulation in 3T3-L1 adipocytes by suppressing lipogenesis - Ji Li; Xuedong Wang; Xiangyu Meng; Xin Zhou; Han Huang; Yi Feng; Yujie Fu; Xinxin Liu; Bo Yu (Chemico-Biological Interactions, 2023)

Constructing Z-scheme NiMoO4@Co3O4 core-shell heterogeneous architectures with prominent photoelectrocatalytic performance toward water purification - Huijun Li; Pengyuan Wang; Enxi Jin; Wenbo Lan; Chi Han; Guowen Wang; Dezhi Huang; Xinxin Zhang; Hongchao Ma (Chemosphere, 2023)

Boosting oxygen reduction with coexistence of single-atomic Fe and Cu sites decorated nitrogen-doped porous carbon - Heng Liu; Luozhen Jiang; Yamin Wang; Xinxin Wang; Javid Khan; Yanlin Zhu; Jiamin Xiao; Lina Li; Lei Han (Chemical Engineering Journal, 2023)

Assessment of the inhalation exposure and incremental lifetime cancer risk of PM2.5 bounded polycyclic aromatic hydrocarbons (PAHs) by different toxic equivalent factors and occupancy probability, in the case of Xi’an - Yumeng Wang; Zedong Wang; Jingzhi Wang; Runyu Wang; Xinxin Ding; Neil McPherson Donahue; Zhibao Dong; Ge Ma; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2022)

Study on mechanical properties and elasto-brittle-plastic constitutive model of hard brittle rock based on conventional triaxial test - Xinxin Fang; Han Tong; Jiaming Feng; Yanqiu Wang; Xiaowei Ni; Shaoyong Hou; Kang Bie (Arabian Journal of Geosciences, 2022)

A Full Evaporation Static Headspace Gas Chromatography Method with Nitrogen Phosphorous Detection for Ultrasensitive Analysis of Semi-volatile Nitrosamines in Pharmaceutical Products - Jinjian Zheng; Christine L. Kirkpatrick; Daniel Lee; Xinxin Han; Ana I. Martinez; Kimberly Gallagher; Rebecca K. Evans; Sanjay V. Mudur; Xihui Liang; Jennifer Drake; Leah A. Buhler; Mark D. Mowery (The AAPS Journal, 2022)
The recent detection of potent carcinogenic nitrosamine impurities in several human medicines has triggered product recalls and interrupted the supply of critical medications for hundreds of millions of patients, illuminating the need for increased testing of nitrosamines in pharmaceutical products. However, the development of analytical methods for nitrosamine detection is challenging due to high sensitivity requirements, complex matrices, and the large number and variety of samples requiring testing. Herein, we report an analytical method for the analysis of a common nitrosamine, N-nitrosodimethylamine (NDMA), in pharmaceutical products using full evaporation static headspace gas chromatography with nitrogen phosphorous detection (FE-SHSGC-NPD). This method is sensitive, specific, accurate, and precise and has the potential to serve as a universal method for testing all semi-volatile nitrosamines across different drug products. Through elimination of the detrimental headspace-liquid partition, a quantitation limit of 0.25 ppb is achieved for NDMA, a significant improvement upon traditional LC-MS methods. The extraction of nitrosamines directly from solid sample not only simplifies the sample preparation procedure but also enables the method to be used for different products as is or with minor modifications, as demonstrated by the analysis of NDMA in 10+ pharmaceutical products. The in situ nitrosation that is commonly observed in GC methods for nitrosamine analysis was completely inhibited by the addition of a small volume solvent containing pyrogallol, phosphoric acid, and isopropanol. Employing simple procedures and low-cost instrumentation, this method can be implemented in any analytical laboratory for routine nitrosamine analysis, ensuring patient safety and uninterrupted supply of critical medications.

Downregulated hypoxia-inducible factor 1α improves myoblast differentiation under hypoxic condition in mouse genioglossus - Yun Lu; Jiaqi Mao; Xinxin Han; Weihua Zhang; Yuanyuan Li; Yuehua Liu; Qiang Li (Molecular and Cellular Biochemistry, 2021)

Comparative analysis of transcriptomic profiling to identify genes involved in the bulged surface of pear fruit (Pyrus bretschneideri Rehd. cv. Yuluxiangli) - Baopeng Ding; Tingting Liu; Chaohui Hu; Yuqin Song; Ruijie Hao; Xinxin Feng; Tingting Cui; Youzhi Han; Liulin Li (Physiology and Molecular Biology of Plants, 2021)

Identification, characterization, and functional prediction of circular RNAs in maize - Yang Han; Xinxin Li; Yan Yan; Ming-Hua Duan; Jian-Hong Xu (Molecular Genetics and Genomics, 2020)

Partial substitution of chemical fertilizers with organic amendments increased rice yield by changing phosphorus fractions and improving phosphatase activities in fluvo-aquic soil - Muhammad Qaswar; Rushan Chai; Waqas Ahmed; Huang Jing; Tianfu Han; Kailou Liu; Xinxin Ye; Yongmei Xu; Christian Kofi Anthonio; Huimin Zhang (Journal of Soils and Sediments, 2020)

Binding of clenbuterol to HSA and FTO: a spectroscopic analysis and molecular docking - Zechun Wang; Xinxin Han; Ning Wang; Ruiyong Wang; Junbiao Chang (Medicinal Chemistry Research, 2018)

Study of the Binding between Camptothecin Analogs and FTO by Spectroscopy and Molecular Docking - Ting Ren; Zechun Wang; Lijiao Zhang; Ning Wang; Xinxin Han; Ruiyong Wang; Junbiao Chang (Journal of Fluorescence, 2017)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

Evolutionary history of Apocheima cinerarius (Lepidoptera: Geometridae), a female flightless moth in northern China - Shuxian Liu; Nan Jiang; Dayong Xue; Rui Cheng; Yanhua Qu; Xinxin Li; Fumin Lei; Hongxiang Han (Zoologica Scripta, 2016)
The alterations in the phylogeographical structures of insects in response to the uplift of the Qinghai–Tibet Plateau and the Quaternary glaciations in eastern Asia, particularly in northern China, remain largely unknown. In this study, we selected Apocheima cinerarius , a moth with flightless females, using molecular data (complete mitochondrial genomes and nuclear data) and ecological niche modelling ( ENM ) to investigate the effects of paleoclimatic changes on the evolutionary history of insects in the area of northern China. The phylogenetic tree of complete mitochondrial genomes indicated that there were two lineages, the western and eastern lineages. The nuclear gene analyses also detected unique haplotypes in each lineage. Time of the most recent common ancestor ( TMRCA ) of the two lineages was approximately in Early–Middle Pleistocene. Bayesian skyline plots revealed that the western lineage underwent a population expansion event after the Last Glacial Maximum, whereas the eastern lineage underwent expansion between the Last Interglacial and the Last Glacial Maximum. Our results suggest that A. cinerarius expanded eastward from western sites until the moth was distributed across the entire region of northern China. Then, A . cinerarius underwent contraction into isolated glacial refugia followed by subsequent expansion driven by Pleistocene climate changes, which established a narrow sympatric area. Our results indicate that the Quaternary environmental fluctuations had profound influences on the diversification and demography of an insect in northern China, and the same species in north‐western China and north‐eastern China have different demographic histories.

The sero-prevalence of anti-adenovirus 5 neutralizing antibodies is independent of a chronic hepatitis B carrier state in China - Dao Huang; Marie Hennequi; Alexei Elvachev; Thierry Menguy; Nathalie Silvestre; DeMin Yu; Yue Han; Geneviève Inchauspé; Xinxin Zhang; Ren Zhu (Archives of Virology, 2015)

High mobility group box-1 induces migration of vascular smooth muscle cells via TLR4-dependent PI3K/Akt pathway activation - Jian Yang; Lihua Chen; Jun Yang; Jiawang Ding; Han Rong; Wusong Dong; Xinxin Li (Molecular Biology Reports, 2012)